2017
DOI: 10.1002/macp.201700039
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection of pH and Biomolecular Interactions at Micromolar Concentrations Aided by a Trivalent Diacetylene-Based Vesicle

Abstract: A trivalent tris‐(alkylenediynoic acid) is developed as a new monomer to prepare a poly(tris‐(diacetylene)). Alkylenediynoic moieties, covalently linked to the gallic acid, lead to a high propensity for polymerization, resulting in blue poly(tris‐(diacetylene)), within less than 20 s of UV irradiation as aq. vesicle solution and as thin film. The vesicle undergoes reversible thermochromism between room temperature and 95 °C. The corresponding chromism changes are blue‐to‐red‐to‐orange during heating and revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Copyright 2018 The Royal Society of Chemistry. Panel c adapted with permission from refs and . Copyright 2016 and 2017, respectively, John Wiley and Sons.…”
Section: Nonlinear Diacetylenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2018 The Royal Society of Chemistry. Panel c adapted with permission from refs and . Copyright 2016 and 2017, respectively, John Wiley and Sons.…”
Section: Nonlinear Diacetylenesmentioning
confidence: 99%
“…Singh et al prepared a hyperbranched diacetylene monomer 1 with three diacetylenes covalently linked to a gallic acid (Figure ci). It was found that the PDA derived from this monomer showed an excellent reversible colorimetric response to temperature in solution (20–95 °C) and in a thin film (20–220 °C), accompanied by responsiveness to pH. When the carboxylic group of the garlic acid was replaced with poly­(alkyl aryl ether) dendrons to obtain monomer 2, the reversible thermochromism was further improved to 300 °C, as a result of enhanced interactions provided by the dendrons .…”
Section: Nonlinear Diacetylenesmentioning
confidence: 99%
“…Diacetylenes are a well-studied class of photoactive compounds, with 10,12-pentacosadiynoic acid (PCDA, Figure ) as a common example . Irradiation of PCDA with ultraviolet light, X-rays, or γ-radiation results in photopolymerization to give a polydiacetylene with an alternating ene-yne backbone. , This monomer to polymer conversion is accompanied by a visible color change from colorless to blue, with additional perturbations further changing the color of the polydiacetylene from blue, to purple, red, yellow, and sometimes green depending on the polymer conformation and ordering, and hence extent of delocalization of the conjugated backbone. Diacetylenes undergo topochemical photopolymerization not only as crystalline solids but also in semiordered media such as liquid crystals, thin films, vesicles, and gels. The chromic properties of the resulting polydiacetylenes are typically exploited in dosimeters, biosensors, and chemosensors. …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] PDA polymers exhibit characteristic thermochromatic properties, as a result these polymers are utilized in a number of biological, interfacial, and materials applications. [4][5][6][7][8][9][10][11][12][13][14][15] Inducing anisotropy in PDAs would result in a liquid crystalline (LC) behavior, [16][17][18] as illustrated through functionalizing the polymers with moieties such as aromatic dicarboxylic acids, [13,18,19] biphenyl esters, [20,21] cyanostilbene, [22] and azobenzene. [23] Incorporation of amphiphilicity in a molecule is a fruitful route to enable mesomorphic behavior.…”
Section: Introductionmentioning
confidence: 99%